The effects of self-esteem and vulnerability to illness on perceived quality of "pure" water (2003)
This research was carried out to find out the effects of self-esteem and illness vulnerability on perception of quality of water packaged in cellophane bags, popularly known in Nigeria as “pure water”. The interest in “pure water” stemmed from the increase in the packaging, marketing, and consumption of the commodity in Nigeria and the health implications for millions of the nation’s citizens and residents who consume pure water. Participants in the research, whose design was ex post facto, were drawn from the general student population of the University of Ibadan, Nigeria. They were two hundred in number consisted of one hundred males and one hundred females aged between 17 to 32 years. All participants were resident on the campus of the University of Ibadan. In all, four hypotheses were tested using t-test and two-way analysis of variance (ANOVA) statistics. Findings in respect of hypothesis one revealed a significant difference between the mean scores of people with high self –esteem and the mean score of those with low self esteem in their perception of the quality of pure water. Thus, the hypothesis was supported (t =3.50, df = 198, P<.05). In hypothesis two, findings indicated that there was no significant difference between the mean scores of people with high self-esteem and the mean scores of people with low self esteem in their perception of the quality of bottled water (t-=0.66, df = 198, p> .05). Thus the hypothesis was not supported. With regards to hypothesis three, results showed that there was no significant difference between the mean scores of people with high illness vulnerability and the mean scores of people with low illness vulnerability as regards their perception of the quality of pure water. Similarly, the hypothesis was not supported. Lastly in hypothesis four, results showed that although there was a significant independent effect of self-esteem on the perception of the quality of pure water, the interaction of self-esteem and illness vulnerability did not produce significant effect on people’s perception of the quality of pure water. Thus, hypothesis four was only partially supported. It was suggested that since self-esteem and illness vulnerability individually affected people’s perception of the quality of pure water, it will be advisable for producers of pure water to improve on the quality and packaging of their products towards wider market coverage, maximum profitability, and consumer health.